2023
DOI: 10.1097/ppo.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Exosomes and the Role of Liquid Biopsy in Human Papillomavirus Oropharyngeal Squamous Cell Carcinoma

Abstract: The global incidence of human papillomavirus–positive (HPV+) head and neck squamous cell carcinoma (HNSCC) has surged in recent decades, with HPV+ HNSCC accounting for >70% of oropharynx cancers in the United States. Its incidence in men has surpassed that of HPV+ cervical cancer in women, and reliable assays are needed for early detection and to monitor response to therapy. Human papillomavirus–positive OPSCC has a more favorable response to therapy and prognosis than HPV-negative (HPV−) HNSCC, motivating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…These assays leverage ultrasensitive sequencing methods to detect cell-free HPV ctDNA shed from the primary tumor or metastatic deposits into circulation [19][20][21] . Numerous robust studies have shown promising sensitivity, specificity, and positive and negative predictive values of these assays for detecting locoregional and distant recurrences of HPV-related OPSCC [22][23][24][25] . We direct the reader to Kuhs et al for a contemporary review of published plasma HPV ctDNA test parameters [19] .…”
Section: Liquid Biomarkers For Surveillance Of Hpv-related Opsccmentioning
confidence: 99%
See 1 more Smart Citation
“…These assays leverage ultrasensitive sequencing methods to detect cell-free HPV ctDNA shed from the primary tumor or metastatic deposits into circulation [19][20][21] . Numerous robust studies have shown promising sensitivity, specificity, and positive and negative predictive values of these assays for detecting locoregional and distant recurrences of HPV-related OPSCC [22][23][24][25] . We direct the reader to Kuhs et al for a contemporary review of published plasma HPV ctDNA test parameters [19] .…”
Section: Liquid Biomarkers For Surveillance Of Hpv-related Opsccmentioning
confidence: 99%
“…Plasma HPV ctDNA monitoring has shown robust statistical parameters for prediction and detection of locoregional and distant recurrences across several HPV-related OPSCC subgroups, including those with significant tobacco use history [20,21,25] . While no published study has been powered to examine this population specifically, preliminary results suggest that the kinetics of plasma HPV ctDNA levels accurately reflect the unique biology and disease activity of intermediate-risk HPV-related OPSCC [19] .…”
Section: A Biologically Distinct Populationmentioning
confidence: 99%
“…These assays can use saliva, urine, or plasma-based biomarkers to improve diagnosis, treatment, and surveillance paradigms, but progress in developing robust and reliable liquid biopsy techniques for patients with HPV-negative HNSCC is more arduous. Nonetheless, preclinical and translational efforts are advancing liquid biopsy techniques for patients with HPV-negative tumors …”
mentioning
confidence: 99%